The Development of Pseudocapacitive Properties in Nanosized-MoO2. Issue 5 (3rd February 2015) - Kim, Hyung-Seok; Cook, John B.; Tolbert, Sarah H.; Dunn, Bruce
Abstract : Pseudocapacitive charge storage materials offer the opportunity to bridge the gap between high energy density battery materials and high power density electrical double layer capacitor materials through the rational design of transition metal oxide nanoscale architectures. The research reported in this paper describes the origins and development of pseudocapacitance in MoO2 . Micron-size particles of MoO2 exhibit a reversible monoclinic to orthorhombic phase transition upon lithium insertion/deinsertion, however, this phase transformation is suppressed when using 15 nm nanocrystals of MoO2 . The nanoscale MoO2 exhibits pseudocapacitive behavior and achieves substantially better energy storage kinetics than the corresponding bulk material. Such size-dependent electrochemical behavior is an essential feature of an extrinsic pseudocapacitor material. The high power capability of nanoscale MoO2 is improved further by synthesizing hybrid materials in which MoO2 nanoparticles are grown on reduced graphene oxide (RGO) scaffolds. Electrode architectures containing MoO2 -RGO hybrid materials preserve the pseudocapacitance of MoO2 as lithium capacities of nearly 150 mAh g −1 are obtained at a rate of 50 C.